Hormesis Promotes Evolutionary Change - David Costantini (SAGE Publishing, 2019)
Exposure to moderate environmental stress is one important source of evolutionary change. This evidence would support the hypothesis that hormesis is an evolutionary expectation. In this short review, I discuss relevant examples of genetic and phenotypic responses to moderate stress exposure that are compatible with hormesis and with paradigms of evolutionary theory such as evolutionary rescue or phenotypic plasticity. Genetic recombination, nonlethal mutations, activity of transposable elements, or gene expression are some of the molecular mechanisms through which hormesis might enable organisms to maintain or even increase evolutionary fitness in stressful environments. These mechanisms span the tree of life from plants to vertebrates.